Interpretasi Hadis Kesehatan Mental dan Dampaknya bagi Neuropsikologi - Surya Azhari; Sulaiman Muhammad Amir (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to interpret the Prophetic hadiths related to mental health and examine their relevance to modern neuropsychology. It employs a qualitative approach using library research with a thematic (mawdu’i) method. The data were collected from hadiths contained in the Kutub al-Sittah, classical hadith commentaries (sharh), and relevant literature on psychology, neuropsychology, and neuroscience. The analysis involved takhrij of the hadiths, interpretation based on the explanations of classical scholars, and integration with contemporary neuropsychological theories. The findings reveal that hadiths concerning anger regulation, optimism, patience, remembrance of Allah (dhikr), and husn al-zhann (positive expectation toward Allah) embody principles of mental health that are consistent with psychological and neurobiological mechanisms. Anger regulation is associated with self-regulation and reduced amygdala activity; patience strengthens resilience by lowering cortisol levels; gratitude and optimism enhance positive emotions through dopamine activation; tawakkul reduces anxiety by optimizing prefrontal cortex function; while dhikr induces relaxation through activation of the parasympathetic nervous system. These findings indicate that the values embedded in the hadiths transform religious understanding into positive cognitive patterns and adaptive behaviors, which subsequently influence brain activity through neuroplasticity and promote mental well-being. This study concludes that hadiths serve not only as normative and spiritual guidance but also as scientifically relevant sources for the development of mental health from a neuropsychological perspective, thereby reinforcing the integration of hadith studies with modern neuroscience.